Nurses’ Perception of Work-Environment Uncertainty and Readiness for Organizational Change - Alsolami, Aishah; Alkorashy, Hanan; Alfaki, Mysara; Alkarani, Ahmed (UI Scholars Hub, 2023)
Background: Healthcare organizations have a dynamic work-environment that changes constantly. This study aimed to explore whether there is a relationship between work-environment uncertainty and nurses’ readiness to participate in organizational change. Methods: A cross-sectional study was conducted at two tertiary hospitals. The sample size was 222 nurses. A self-report questionnaire was adopted, translated to Arabic, and used for collecting data; it consists of three scales, personal data sheet, organizational readiness for implementing change scale, and perceived environmental uncertainty in hospitals scale. Descriptive statistics t-test and analysis of variance were used to analyze the data. Results: The level of agreement with the change efficacy statements with the total mean percentage of nurses’ readiness for organizational change (change efficacy) was 67.0%, and it was slightly higher than the commitment statements, in which the total mean percentage of nurses’ readiness for organizational change (change commitment) was 64.2%. In addition, one of the work-environment uncertainty dimensions, which is the individual attribute (need for information), positively correlated with the organizational readiness to change. Conclusions: The organizational readiness to implement organizational change is high. Environmental complexity was highly perceived among nurses as one of the work-environment uncertainty dimensions. An organizational environment considering employee characteristics must be developed to improve their knowledge, skills, and attitude to adapt to change and uncertainty.